Exercise, Training & Health - Carthaus A; Görgens C; Knoop A; Geyer H; Thevis M (Deutsche Zeitschrift für Sportmedizin, 2022)
Rationale: Anti-SARS-CoV-2 antibody responses elicited by infection or vaccination vary among individuals and over time. Their knowledge is of particular importance in, amongst others, elite sport. Can dried blood spots serve as a minimally-invasive, low-cost, decentralized tool to monitor the quantitative antibody response and thus represent an alternative to full blood tests?Methods: Cross-validation of dried blood and venous blood samples of 27 individuals post-infection and 96 individuals post-vaccination, longitudinal antibody monitoring of 27 individuals after vaccination using different vaccines and vaccine schedules and detection of seropositive individuals in a cohort of 557 people using self-collected DBS (dried blood spots) and two commercial immunoassays.Findings: Plasma and DBS values were highly correlated allowing for extrapolation of plasma values from DBS using a factor of a least 10 following the presented procedure. Capillary volumetric sampling and self-sampling produced reliable results. After vaccination, participants showed heterogenous antibody responses but a consistent increase after the second dose. DBS allowed for the analysis of a huge sample volume in a timely manner by limited laboratory personnel.Discussion: DBS offer the possibility of infection and vaccination traceability of individuals and cohorts via minimally-invasive self-sampling. This way, they allow to screen and monitor the presence and evolution of anti-SARS-CoV-2 antibodies in a qualitative and quantitative manner. Using two commercial, automated assays enables large-scale and frequent testing, global implementation and comparability of results.Key Words: Coronavirus, Pandemic, Diagnostics, Immunity, DBS